A Distributed Parallel Algorithm for Magnetotelluric Forward Modeling - Cheng Tang-pei; Wang Qun (2008 International Conference on Computer Science and Software Engineering : 12-14 December 2008, 2008)
We present a distributed parallel algorithm for magenetotelluric forward modeling. The Maxwell's equation is deduced to a linear equation and the GreenField algorithm is introduced to solve it. Since magenetotelluric forward modeling processes the data by frequency which internally has respectable parallelism, we opt for the domain decomposition strategy to deal with it. The performance of this algorithm has been evaluated and the result demonstrates great efficiency, flexibility and scalability.